2022
DOI: 10.1007/s10530-022-02849-9
|View full text |Cite
|
Sign up to set email alerts
|

High habitat invasibility unveils the invasiveness potential of water frogs

Abstract: Determining the invasibility of habitats by alien species is crucial for understanding their spread potential, the habitats the most at risk and to implement adequate management actions. This is urgent for introduced taxa that show high invasion potential across broad geographical scales. We here assess these processes in invasive Pelophylax water frogs which are widespread colonizers across Western Europe and for which the invasibility of habitats remains to be quantified. Specifically, we used hierarchical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…More recently, molecular surveys aimed at tracing emerging biological invasions, notably by the marsh frogs (P. ridibundus complex), following uncontrolled introductions linked in part to the international trade for the frog leg industry (e.g., Bellati et al, 2023;Dufresnes et al, 2018;Dufresnes & Dubey, 2020;Holsbeek et al, 2008). Today, Pelophylax invaders are becoming a strong conservation concern, due to their broad habitat tolerance (Denoël et al, 2022), potential performances under future climate change (Padilla et al, 2023), fierce predation on native batrachofauna (Pille et al, 2021) and invertebrates (Pille et al, 2023), potential vectors of amphibian diseases such as chytridiomycosis (Baláž et al, 2014), and the risk to deregulate autochthonous hybridogenetic systems through hybridization and competition (Holsbeek & Jooris, 2010;Quilodrán et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, molecular surveys aimed at tracing emerging biological invasions, notably by the marsh frogs (P. ridibundus complex), following uncontrolled introductions linked in part to the international trade for the frog leg industry (e.g., Bellati et al, 2023;Dufresnes et al, 2018;Dufresnes & Dubey, 2020;Holsbeek et al, 2008). Today, Pelophylax invaders are becoming a strong conservation concern, due to their broad habitat tolerance (Denoël et al, 2022), potential performances under future climate change (Padilla et al, 2023), fierce predation on native batrachofauna (Pille et al, 2021) and invertebrates (Pille et al, 2023), potential vectors of amphibian diseases such as chytridiomycosis (Baláž et al, 2014), and the risk to deregulate autochthonous hybridogenetic systems through hybridization and competition (Holsbeek & Jooris, 2010;Quilodrán et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Widely distributed from northwestern Africa to Japan, Palearctic water frogs of the genus Pelophylax offer great opportunities for large-scale studies in biogeography (Akın et al, 2010;Komaki et al, 2015;Lymberakis et al, 2007;Nicolas et al, 2015) and invasion biology (Denoël et al, 2022). From a molecular perspective, new biogeographic paradigm for the Palearctic since the Paleogene, notably by attributing a prominent role to the dynamics of the Paratethys, a vast paleo-sea that extended over most of Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the non‐native nature of the studied marsh frog populations, their wide fundamental trophic niche combined with the substantial number of feeding opportunities in ponds and along their shores results in the high potential invasiveness of marsh frogs. A recent study demonstrated the invasiveness potential from a habitat selection perspective across the landscape (Denoël et al, 2022). The present work highlights that this invasion success could also be enhanced by the trophic generalism of marsh frogs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated the invasiveness potential from a habitat selection perspective across the landscape (Denoël et al, 2022).…”
Section: Feeding Opportunities Across the Water-air Interface Of Pondsmentioning
confidence: 99%